The Effect of Work-based Benefits and Demand on Engagement and Well-being as Mediated by Work-University Facilitation and Conflict Among Working Students in Indonesia - Sinaga, Iin Yessica Putrilima; Rachmawati, Riani (The South East Asian Journal of Management, 2021)
Research Aims: This study uses a depletion and enrichment model to examine the effect of role conflict whereby work-based benefits and demands on a person’s first role (workers) influence facilitation and conflict on their second role (university student), and influence the students’ engagement and well-being. Design/methodology/approach: This research tested whether facilitation and conflict acted as mediators between benefits and demands with engagement and well-being. The hypotheses were tested using 290 respondents (63.4% were female with an average age of 23.4 years) who were working while studying. Research Findings: The results suggested that benefits were associated positively with facilitation; demands were associated with more conflict; and facilitation was associated with engagement and well-being. Theoretical Contribution/Originality: This study supports the enrichment model that the first role will energize and facilitate students in the second role, and influences engagement and well-being. Whereas in the depletion model, demands have a positive influence on conflict, but do not have a negative impact on the engagement and well-being. Managerial Implication in the South East Asian context: This study shed lights on understanding that working while studying has its own benefits. The experience at work can become an asset to carry as students enter the full-time job market while accelerating their launch into full-time career. Research limitation & implications: Due to time constraints, the researchers only examined the relationship between variables, while previous research tested the dimensions contained in the variables. Most respondents come from universities located in Java and less is known about the experiences of working students in other islands.